2015
DOI: 10.1007/s00066-015-0888-1
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous integrated vs. sequential boost in VMAT radiotherapy of high-grade gliomas

Abstract: Our analysis shows that the SIB method offers advantages over the SEB method in terms of sparing OARs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Farzin et al compared SIB vs SEB in 20 patients with high-grade gliomas. In the SIB method, the PTV received 54 Gy in 30 fractions with 1.8Gy dose per fraction, while the tumor bed received 60 Gy in 2 Gy per fraction [22]. There results demonstrated that the SIB and SEB were equivalent in target coverage, but the SIB was significantly superior to the SEB for almost all the OARs sparing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Farzin et al compared SIB vs SEB in 20 patients with high-grade gliomas. In the SIB method, the PTV received 54 Gy in 30 fractions with 1.8Gy dose per fraction, while the tumor bed received 60 Gy in 2 Gy per fraction [22]. There results demonstrated that the SIB and SEB were equivalent in target coverage, but the SIB was significantly superior to the SEB for almost all the OARs sparing.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in addition to "physical sparing" of OARs, the simultaneous integrated boost (SIB) method can also offer the possibility of a "biological sparing" as in SIB method, the single dose per fraction to the PTV not boost tumor volume (BTV) was lower when compared with the SIB. That might be of interest in patients with brain tumors with longer life expectancies and when considering that in the PTV there is a comparatively high probability of irradiation of subvolumes of relatively sensitive OARs [19]. The Primary Objective of the study was to compare the dosimetric coverage of the Planning target volumes (PTV) and sparing the critical structures and organs at risk (OARs) using different delivery methods of radiation to Boost Tumor volume (BTV) for high grade Glioma, using sequential boost (SEB) vs. simultaneous integrated boost (SIB) using VMAT.…”
mentioning
confidence: 99%
“…Before the arrival of IMRT, the SeqB method was mostly used, within the 3D conformal irradiation technique to treat high-grade gliomas. With the SIB method, the dose per fraction to the PTV is lower when compared with the SEB, delivers an enhanced dose to the gross tumor volume and has a greater potential of sparing of organs at risk (Figure 8) [33][34][35][36][37]. Whole brain radiotherapy is the most common palliative treatment and has always been considered the standard treatment for patients with brain metastases.…”
Section: Radiotherapymentioning
confidence: 99%
“…In humans, SIB protocols have been investigated for different tumor types and anatomical regions, including brain tumors. 14 , 15 , 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%